The Application Of Artificial Intelligence In Nursing At Saudi Arabia: A Systematic Review (The Review of Diabetic Studies, 2024)
This systematic review is to offer a comprehensive overview of the current state of artificial intelligence (AI) use in nursing practice in the Kingdom of Saudi Arabia. The review focuses on identifying key challenges, analyzing nurses' attitudes and perceptions of AI, investigating knowledge gaps and areas for improvement in AI integration, examining the benefits and limitations of AI applications in nursing, and making recommendations to improve AI adoption in nursing. Practice. A comprehensive search of internet databases from 2020 to 2024 yielded six relevant studies. The findings show various levels of preparation and acceptance of AI among Saudi nurses, underlining the importance of educational and training initiatives to bridge knowledge gaps and address concerns about career displacement and dehumanization of care. Collaboration among stakeholders is emphasized as critical to the ethical integration of AI into nursing practice. The research underlines the significance of a complete approach to implementing artificial intelligence in nursing to improve patient care outcomes and stimulate innovation in the Saudi healthcare system. Further research is needed to broaden the scope of the study and investigate a broader range of approaches in order to gain a more comprehensive understanding of the use of AI in nursing practice.